Rapid Detection and Typing of Actinobacillus pleuropneumoniae Serovars Directly From Clinical Samples: Combining FTA® Card Technology With Multiplex PCR - Stringer, Oliver W.; Bossé, Janine T.; Lacouture, Sonia; Gottschalk, Marcelo; Fodor, László; Angen, Øystein; Velazquez, Eduardo; Penny, Paul; Lei, Liancheng; Langford, Paul R.; Li, Yanwen (Frontiers in Veterinary Science, 2021)
Actinobacillus pleuropneumoniae, the causative agent of porcine pleuropneumonia, is highly contagious and responsible for high morbidity, mortality and economic losses in the swine industry worldwide, but quick serotyping and diagnosis are still not widely available. In this study, we sought to validate the use of Whatman FTA® cards for collection and processing of A. pleuropneumoniae isolates, or porcine lung tissue samples, for direct use in diagnostic multiplex PCRs. We have optimized the processing of 3 mm discs punched from FTA® cards loaded with cultured A. pleuropneumoniae, or imprinted on lesioned regions of lung tissue, with only three distilled water washes before addition into our APP-mPCR assay for rapid, low-cost identification and serotyping. DNA captured on FTA® cards generated the same diagnostic PCR results as DNA extracted using commercial kits for 85 A. pleuropneumoniae clinical isolate cultures and 22 lung samples. Additionally, bacterial DNA bound to FTA® cards was detectable by PCR after six months of storage at 37°C. This study provides simple, efficient, rapid and practical sample processing for detection and molecular serotyping of A. pleuropneumoniae.